2014
DOI: 10.1039/c4cy00192c
|View full text |Cite
|
Sign up to set email alerts
|

Bis(imino)acenaphthene (BIAN)-supported palladium(ii) carbene complexes as effective C–C coupling catalysts and solvent effects in organic and aqueous media

Abstract: Significant solvent effects in the Suzuki–Miyaura coupling reaction are described for the case of two new N-heterocyclic carbene-supported palladium(ii) complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…In the literature, there are not available apparent information about activation energy of the heterogeneous catalyzed Suzuki reaction of Brac and FBA in aqueous media. Crawford et al synthesized 1,2‐acenaphthenyl NHC‐supported palladium(II) catalysts ((BIAN)‐supported palladium(II) carbene complexes) and used them in heterogeneous catalyzed Suzuki reaction of bromobenzaldehyde and FBA in aqueous media . The activation energies of these catalytic systems were determined to be in the range of 111‐116 kJ mol −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are not available apparent information about activation energy of the heterogeneous catalyzed Suzuki reaction of Brac and FBA in aqueous media. Crawford et al synthesized 1,2‐acenaphthenyl NHC‐supported palladium(II) catalysts ((BIAN)‐supported palladium(II) carbene complexes) and used them in heterogeneous catalyzed Suzuki reaction of bromobenzaldehyde and FBA in aqueous media . The activation energies of these catalytic systems were determined to be in the range of 111‐116 kJ mol −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Crawford et al synthesized 1,2-acenaphthenyl NHC-supported palla-dium(II) catalysts ((BIAN)-supported palladium(II) carbene complexes) and used them in heterogeneous catalyzed Suzuki reaction of bromobenzaldehyde and FBA in aqueous media. 48 The activation energies of these catalytic systems were determined to be in the range of 111-116 kJ mol −1 . When these results compared with the present study, it can be seen that activation energies which determined by Crawford and co-workers are significantly larger than the poly(AAm-co-AMPS)-based NHC-Pd-pyridine catalyzed Suzuki reaction of Brac and FBA.…”
Section: Activation Energymentioning
confidence: 99%
“…In 2014, Humphrey and co‐workers reported mixed NHC/phosphine [Pd(BIAN‐NHC)(PPh 3 )Cl 2 ] complexes 8 – 9 and evaluated their reactivity in the Suzuki–Miyaura cross‐coupling of aryl halides under aqueous conditions (Scheme 5). [35] The performance of catalysts 8 – 9 was also evaluated in non‐polar solvents. Interestingly, it was found that water and toluene promoted catalyst decomposition to yield a new heterogeneous species, while both catalysts were considerably more stable in dichloromethane.…”
Section: Palladium‐bian‐nhc Complexesmentioning
confidence: 99%
“…Nevertheless, enormous progress has been made improving the efficiency of Suzuki catalysts and extremely high turnover frequencies and turnover number can be achieved and the nature of the solvent plays an important role with respect to catalyst stability. 58 The active catalyst in the Suzuki reaction is based on a palladiumIJ0) species ( Fig. 15 shows a generic mechanism for the reaction).…”
Section: C-c Coupling Reactionsmentioning
confidence: 99%